Academic library buildings in the electronic age a study of planning and design considerations of selected academic library buildings in the Philippines completed between 2001 and 2013 - Gado, Marlon G. 1982-; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2015)
Academic library buildings are important centers for the efficient delivery of library services. In this regard, this study sought to determine the planning and design considerations that led to either satisfaction or dissatisfaction with the academic library buildings completed between 2001 and 2013. In doing so, 10 academic library planning teams were surveyed using a questionnaire adapted from Sannwald (2009) Bennet, (2003) and Stewart, (2009). This study utilized the descriptive method of research. The data gathered from the survey were ranked with "strongly considered" as the highest and "never considered" as the lowest rank.
The survey revealed the following findings
Physical structure: (1) Library building planning teams were satisfied with majority of the planning activities they conducted. (2) Consultation with university administrators is a very important factor in most aspects of library planning activities. (3) The main considerations for the building consultant, architect and contractor are their track records and ability to commit to the project from start to finish. (4) The selected academic library buildings are centrally located. (5) Security of the user, collections and equipment was the utmost consideration in most public areas, such as entrance, outdoor book media returns, reserve facilities, special collections/ rare books/ archives facilities, media production and presentation laboratory, delivery dock, bicycle rack, parking, interior storage and baggage facilities. (6) The durability of materials used was the top consideration for furniture and floor finishes. (7) The use of natural light was widely considered in the selected academic library buildings. (8) The library building planning teams ensured that the library design preserves the natural outdoor environment and promotes healthful indoor habitat. (9) The library building design had no adverse impact on the natural state of the air, land and water by using resources that minimize pollution and waste.
Technological infrastructure and other IT services: (1) The institutional wireless program and the location of workstations were the top considerations for planning telecommunication entrances and closets, horizontal pathways and workstation connections; (2) The compatibility of cabling and outlets to the type of library equipment and media were ensured; (3) The size of the library, collections and spaces were the top considerations for planning the CCTV.
Financial concerns: (1) The utmost financial consideration for planning library buildings was the availability of actual budget specifically set aside for library facilities; and (2) Academic administrators provided adequate funding when they see potential benefits from their investment. A good project proposal helps the library building planning team secure enough funding for the projects.
Thesis(M.L.I.S.)--University of the Philippines, Diliman
Keywords: Library buildings -- Philippines; Library buildings -- Philippines -- Safety measures